ANALISIS FRAMING PEMBERITAAN GLORIFIKASI KEBEBASAN SAIPUL JAMIL DI TRIBUNNEWS.COM - Asti Amalia, Fatiha; Noor Rakhmad, wiwid; Nugroho, Adi (Interaksi Online, 2024)
Saipul Jamil was officially released from prison for child sexual abuse and bribery. This moment drew controversy because the media violated ethics by glorifying the freedom of child sexual abuse perpetrators without thinking about the victims’s trauma. Mass media need to pay attention to journalistic ethics as a guideline in directing the behavior of journalists in carrying out their duties. This study aims to reveal how Tribunnews.com framed the news of Saipul Jamil's freedom. Media frequently have perspectives, ideologies, and media agendas in creating certain frames that influences the audience's perception. The researcher selected 10 news articles from Tribunnews.com from September 2 until 3, 2021. This study's research approach was the framing analysis developed by Zhongdang Pan and M. Kosicki which is classified into two concepts, psychological and sociological. The results of this study found that Tribunnews.com tends to use psychological framing. Journalists can accentuate the more favorable aspects and hide the detrimental aspects. The framing structure in the form of syntax, script, thematic, and rhetoric leads to glorification by highlighting the artist Saipul Jamil, indicated by photos and details of Saipul Jamil's freedom. Tribunnews.com emphasizes Saipul Jamil's freedom, ranging from ceremonies, activities to be carried out, career plans after release, to his experience in prison. This is influenced by capitalistic ideology and celebrity culture to attract audiences and generate as much profit as possible. Because, celebrity life is still a favored topic for the general public. The news of Saipul Jamil's freedom caused pros and cons from various parties and offended Saipul Jamil's victims. Therefore, Tribunnews.com violated article 2, which states that journalists are obliged to consider whether the news should be delivered, so as not to trigger social unrest or offend certain parties. In addition, Tribunnews.com also violated article 5, which state that journalists should be balanced and fair as much as possible, and prioritize accuracy over speed in presenting news. Tribunnews.com tends to present events from one party in order to deliver news quickly to the public